INNOVATIVE REFORM OF PUBLIC ADMINISTRATION: METHODOLOGICAL SUPPORT FOR THE ADOPTION AND IMPLEMENTATION OF THE STRATEGIC DECISIONS - Popov S.A. (Pressing Problems of Public Administration, 2015)
The known managerial situation in terms of structuring problems implementing modernproblems of the effectiveness of the innovative renewal of the public authorities body. In order toensure effective management of innovations in the system selected a rational model of decisionand implementation of the strategic decisions. Fleshed out its stages (training, development,adoption and implementation) and their components, as well as for each of them characterized byan appropriate methodological support.